Intermediate results of combination therapy in patients with oligometastatic non-small cell lung cancer - D. I. Yudin; K. K. Laktionov; D. T. Marinov; V. V. Breder; A. K. Allakhverdiev; T. N. Borisova; A. H. Bekyashev; K. P. Laktionov; V. A. Aleshin; M. S. Ardzinba (Медицинский совет, 2018)
At the present time, a small group of patients with oligometastases (who have a solitary metastatic lesion in another organ along with the primary tumour of the lung) is differentiated among the patients with metastatic lung cancer. A total of 14 patients of the study citied in this article underwent a comprehensive treatment of oligometastatic non-small cell lung cancer (ONSCLC), which included systemic therapy and local influence on solitary metastasis. The median overall survival for this group was 20 months (16.0–32.6, CI 95%). The 1-year and 2-year overall survival rates accounted for 84.5 and 65.7%, respectively. The findings of the study demonstrate the possibilities of an aggressive approach to the treatment of patients with ONLDLC.